Bobwhite Quail Production - Peter A. Skewes; Henry R. Wilson (EDIS)
This publication was developed to assist the seasoned quail producer, as well as to provide a sound base for the novice. It should provide basic information needed in the production of quail for a hobby or for business. This document is CIR879, one of a series of the Department of Animal Sciences, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published August 2003.